2020
DOI: 10.1111/liv.14435
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury during highly pathogenic human coronavirus infections

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐Cov‐2), the pathogen of 2019 novel coronavirus disease (COVID‐19), has posed a serious threat to global public health. The WHO has declared the outbreak of SARS‐CoV‐2 infection an international public health emergency. Lung lesions have been considered as the major damage caused by SARS‐CoV‐2 infection. However, liver injury has also been reported to occur during the course of the disease in severe cases. Similarly, previous studies have shown that live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
836
5
62

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 779 publications
(966 citation statements)
references
References 49 publications
28
836
5
62
Order By: Relevance
“…The present study aimed to analyze SARS-CoV-2-induced ALI, its association with death risk and the prognosis after discharge. The major findings of this study include: (1) ALI is more common in the critically ill COVID-19 patients; (2) Accumulating data demonstrated that SARS-CoV-2 infection caused multiple organ injuries, including myocardial dysfunction, lymphopenia and even acute renal failure [15][16][17]. In the present study, we described ALI among COVID-19 patients.…”
Section: Discussionsupporting
confidence: 49%
“…The present study aimed to analyze SARS-CoV-2-induced ALI, its association with death risk and the prognosis after discharge. The major findings of this study include: (1) ALI is more common in the critically ill COVID-19 patients; (2) Accumulating data demonstrated that SARS-CoV-2 infection caused multiple organ injuries, including myocardial dysfunction, lymphopenia and even acute renal failure [15][16][17]. In the present study, we described ALI among COVID-19 patients.…”
Section: Discussionsupporting
confidence: 49%
“…Previous descriptions of so-called "bystander hepatitis" in the severe acute respiratory syndrome (SARS) coronavirus outbreak of 2002 report viral RNA in the liver parenchyma with histologic findings of hepatocyte apoptosis, mitosis (called out as being particularly prominent), and ballooning. 5,6 The prominent hepatocyte mitosis described in these patients was not observed in our patient, although an occasional mitotic figure could be identified (the significance of this is uncertain in the setting of recent transplantation). The Middle East respiratory syndrome (MERS) coronavirus of 2012 has been associated with elevated liver enzymes with case reports describing peri-venular necrosis and mild portal inflammation.…”
Section: Commentmentioning
confidence: 47%
“…The Middle East respiratory syndrome (MERS) coronavirus of 2012 has been associated with elevated liver enzymes with case reports describing peri-venular necrosis and mild portal inflammation. 6,7 In our case, the most salient finding was an acute hepatitic pattern of injury with prominent clusters of apoptotic hepatocytes. Though this is a non-specific finding, the extent of hepatocyte apoptosis and the large clusters were unusual.…”
Section: Commentmentioning
confidence: 59%
“…Acute respiratory distress syndrome Eyes 39 Conjunctivitis Liver 40,41 Liver injury Systemic circulation (blood) 3 Thrombosis Kidney 19,18 Renal injury Brain/CNS 1,42 CNS symptoms GI tract 13,12 Diarrhea CNS = central nervous system; GI = gastrointestinal. atrophy, myocardial degenerative changes, and expression of viral nucleocapsid in lungs and intestines.…”
Section: Lungs 38mentioning
confidence: 99%